Kinetic regularities of the formation of composite electrolytic coatings containing ultradispersed diamond particles - Tytarenko, V.V.; Zabludovsky, V.O.; Shtapenko, E.Ph.; Tytarenko, I.V. (Physics and Chemistry of Solid State, 2022)
The paper formulates the problem of joint electrolytic co-deposition of metal ions and ultradispersed diamond particles into a metal matrix. It presents the developed mathematical model that describes the mechanism and kinetics of the cathode process, mass transfer of metal ions and ultradispersed diamond particles. A satisfactory correlation with experimental data was obtained. The contribution of the thermal action of laser radiation to the intensification of the process of co-deposition of dispersed particles and metal ions was determined. It was found that the more intense penetration of dispersed phase particles into the forming coating during the laser stimulation of the electrodeposition process is due to the presence of a temperature gradient, which provides an additional supply of metal ions in the irradiation region. Based on the theoretical and experimental studies, we established the regularities of the influence of the number and size of nanoparticles on the strengthening properties of composite metal coatings. It was found that an increase in the temperature of an aqueous electrolyte solution in the cathode region during a laser-stimulated deposition process leads to an increase in the flux density of ultradispersed diamond particles, and, as a result, to an increase in the concentration of the dispersed phase in nickel composite coatings, which contributes to the formation of a finer crystalline structure of coatings, an improvement in adhesion, strength properties and increased wear resistance of coatings.